WEBSITE DEVELOPMENT WITH NEW TECHNOLOGY - Khudoykulov Shakhzod Farkhod Ugli; Ismoiljonov Bekhzod Ikrom Ugli; Akhmedov Dilmurod Akmal Ugli (International Journal of Human Computing Studies, 2020)
This research paper explores the various useful methods and techniques used in the creation of the website. We will take brief information about the website development process with a definition for each one. Next, we will talk about popular Web development platforms, frameworks, languages, and modern tools.